The role of financial statement analysis on decision making in Tanzanian banking industry: The case of CRDB PLC., Dar es Salaam - Komba, Odwina Damas (Mzumbe University, 2024)
A dissertation submitted in partial/fulfillment of the requirement for the award of the Degree of Masters of Science in Accounting and Finance (MSc A&F) of Mzumbe University